Impact of gamma-irradiated silver nanoparticles biosynthesized from Pseudomonas aeruginosa on growth, lipid, and carbohydrates of Chlorella vulgaris and Dictyochloropsis splendida. Issue 1 (1st January 2021) - Shanab, Sanaa Mahmoud Metwally; Partila, Abir M.; Ali, Hamdy Elsayed Ahmed; Abdullah, Mohd Azmuddin
ABSTRACT: In this study, the biosynthesis of extracellular silver nanoparticles (AgNPs) was obtained using Pseudomonas aeruginosasupernatant integrated with gamma radiation. The biosynthesis was confirmed by UV-Vis Spectrophotometer. The Atomic Force Microscopy (AFM) recorded the spherical nanoparticle sizes of 10 nm, while the Dynamic Light Scattering (DLS) recorded the size range of 6.7 to 12.1 nm (84.2%) and the particles were monodispersed. The Gas Chromatography/Mass Spectroscopic analysis of the bacterial filtrate suggested the presence of ethylene glycol derivatives, which may act as a reducing agent. In addition, the impact of synthesized AgNPs on the cell growth and metabolite contents of Chlorella vulgaris and Dictyochloropsis splendida was evaluated. The low AgNPs concentrations (1, 3, and 5 mg L -1 ) enhanced the lipid production but at the expense of cell growth. All AgNPs concentrations however displayed negative effects on the carbohydrates content. The fatty acid profile of the microalgal species studied was significantly affected by the addition of AgNPs. The saturated fatty acids represented the highest composition (61–67%) of the total fatty acids, and palmitic acids (16:0) were dominant (43.06–46.57%). Lipids of this composition could withstand autoxidation during storage and are perfect feedstock for biodiesel and other lipid-based applications.Not StartedCompletedRejected